SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN OBJEK WISATA ACEH MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Kikye Martiwi Sukiakhy; Cut Vita Rajiatul Jummi (J-Icon : Jurnal Komputer dan Informatika, 2021)
The number of tourists visiting Aceh increases every year . This is due to the fact that there are numerous kinds of tourist attraction in Aceh. These tourism objects are scattered from districts to cities in Aceh. Accessibility in reaching these tourist destinations is also effortless. It is challenging to determine which tourism object you want to visit, therefore better search more information prior visit the destination. Afterwards, prospective tourists compare and choose tourism objects that suitable with the criteria. Decision support systems can assist prospective tourists in choosing tourist destinations using the Simple Additive Weighting (SAW) method. The data used in this study derived from internal data as well as external data, several tourist destinations with several criteria to be used are alternatives to be compared. In this study, there are several criteria needed to guide prospective tourists to take decisions, such as distance, cost, facilities, time and age. This study used interviews, literature studies and data analysis method. The criteria for distance and cost are the criteria that have the greatest contribution in determining the best alternative tourist destination in Aceh. Based on the entirely alternatives and criteria in this study, the Baiturrahman Grand Mosque was chosen as the best alternative tourist destination in Aceh with a total preference value of 3. The SAW method is an effective and practical calculating method to determine the best tourist destination in Aceh, therefore the potential tourists will conviniently determine tourist destination that suitable their criteria and desires.